Using grey relational analysis to evaluate resource configuration and service ability for hospital on public private partnership model in China. Issue 2 (29th July 2014) - Li, Xiaoning; Liao, Xinbo; Tan, Xuerui; Wang, Haijing
Abstract : Purpose: – The purpose of this paper is to evaluate resource configuration and service ability in hospital on public private partnership (PPP) model (Chaonan Minsheng Hospital of Guangdong Province), supplying decision-making reference for participants of hospital on PPP model. Design/methodology/approach: – Four model of grey relational analysis (GRA) (Deng's correlation degree, grey absolute correlation degree, grey relative correlation degree and grey comprehensive correlation degree) are applied to evaluate resource configuration and service ability, a total of 11 indicators of hospital on PPP model public hospital and private hospital from 2007 to 2011. Findings: – The paper finds that different GRA models have different results when the paper applied them to evaluate resource configuration and service ability in hospital on PPP model. More than 60 per cent indicators of resource configuration (total six indicators) and service ability (total six indicators) are assessed as "hospital on PPP model ≻ public hospital" or "hospital on PPP model≻ private hospital" from three models of Deng's correlation degree, grey absolute correlation degree and grey comprehensive correlation degree. Practical implications: – Evaluation of resource configuration and service ability for hospital on PPP model with GRA makes results quantified objective and provides reference for decision making and management. GRA makes the comparison of resource configuration and service ability between hospital on PPP model and other model hospitals becoming possible. Originality/value: – The shortcoming for data analysis method of "large sample" is overcome and data analysis method of "small sample" is realized by using GRA, which broaden the method of evaluating hospital on PPP model.